2015
DOI: 10.1186/s12917-015-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-pathological findings of otitis media and media-interna in calves and (clinical) evaluation of a standardized therapeutic protocol

Abstract: BackgroundThe aims of this field trial were to describe the clinical-pathologic findings in calves with otitis media (OM) and media-interna (OMI), to evaluate, through the development of a scoring system, the effectiveness of a standardized therapeutic protocol, and to identify the causative pathogens and their possible correlation with concurrent respiratory disease. All animals underwent physical and neurological examinations at three experimental time points: at diagnosis/beginning of treatment (T0), 1 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Unfortunately, our results indicate that HPCIAs are commonly used to treat otitis. Mycoplasma bovis is mainly found in otitis in calves and the chosen antibiotic has to cover this pathogen [ 41 , 54 , 57 ]. Tetracyclines are suggested as first line antimicrobials by the guidelines, but their efficacy may be limited by resistances [ 7 – 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our results indicate that HPCIAs are commonly used to treat otitis. Mycoplasma bovis is mainly found in otitis in calves and the chosen antibiotic has to cover this pathogen [ 41 , 54 , 57 ]. Tetracyclines are suggested as first line antimicrobials by the guidelines, but their efficacy may be limited by resistances [ 7 – 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in this study, the lack of information about Mycoplasma species present in the TTA samples precludes formulating a hypothesis about their pathogenetic role. Although M. bovis is recognized as a major etiologic agent in BRD and otitis media, less is known about other Mycoplasma spp., e.g., M. dispar and M. bovirhinis , which have been detected less frequently in the bovine respiratory tract [ 23 , 24 , 44 47 ]. It has been suggested that the lack of isolation of these two species could be correlated with an inhibitory effect of other mycoplasmas [ 24 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and chronic infections often become difficult to treat, as in the case of this animal, which had already been wrongly treated with 10% iodine solution as an antiseptic in the auricular pavilion, which can aggravate existing lesions due to a chemical lesion by iodine. Furthermore, the use of 20% oxytetracycline (Oxitetra 20% ® ) in sub-therapeutic doses and the short treatment period led to an ineffective result, as the treatment of otitis media is specific antibiotics used against the frequently isolated pathogens spread in the middle and inner ear, and the duration of therapy is influenced by the chronicity of the disease as well as the pathogens involved, ranging from five days to several weeks [11,17]. Due to aural hematoma and otalgia, photobiomodulation with infrared laser (808 nm) was initially prescribed for the treatment of inflammation and edema.…”
Section: Discussionmentioning
confidence: 99%